Determinants of the Use Long-Term Contraception Method In Banten Province: Secondary Data Analysis of Survey Kinerja Akuntabilitas Program (SKAP) BKKBN in 2019 - Y Yuliwati; Siti Maisaroh; Rd Deden Gumilar Nugraha (Universitas Aisyah Pringsewu, 2021)
The province of Banten population growth rate is higher than the rate of population growth in Indonesia (BPS, 2020) to suppress the growth of population can be controlled with the family planning program, using the method of Long-term contraception. Coverage MKJP Banten Province is still low (17%), compared to the scope of MKJP in (24,6%). The purpose of the research to determine the factors associated with the use of the method of long-term contraception. The type of research used is the quantitative analytical cross-sectional approach. The population is all of WUS in the Province of Banten, while the sample WUS that be acceptors totalled 827 people. Data collection using secondary data. The results showed that the factor associated with the use of MKJP is the age and number of children (P-value less than 0.05). The number of children who owned PUS be the factor most dominant associated with the use of MKJP evidenced by the results of logistic regression double value (OR= 1,980) after the controlled variables age, number of children and maternal Education. The number of children that are owned by couples of childbearing age is something of value which is very important for the decision to wear Long-term contraception.Abstrak: Di provinsi Banten laju pertumbuhan penduduk lebih tinggi dari laju pertumbuhan penduduk di Indonesia BPS 2020) untuk menekan pertumbuhan penduduk dapat dikendalikan dengan program KB, menggunakan metode kontrasepsi jangka Panjang. Cakupan MKJP Provinsi Banten masih rendah (17%), dibandingkan cakupan MKJP secara (24,6%). Tujuan penelitian untuk mengetahui faktor yang berhubungan dengan penggunaan metode kontrasepsi jangka panjang. Jenis penelitian yang digunakan adalah analitik kuantitatif dengan pendekatan cross-sectional. Populasinya adalah seluruh WUS di Provinsi Banten, sedangkan sampelnya WUS yang menjadi akseptor KB berjumlah 827 orang. Pengumpulan data menggunakan data sekunder. Hasil penelitian menunjukan bahwa factor yang berhubungan dengan penggunaan MKJP adalah umur dan jumlah anak (P value kurang dari 0,05). Jumlah anak yang dimiliki PUS menjadi factor yang paling dominan berhubungan dengan pemakaian MKJP dibuktikan dengan hasil uji regresi logistic ganda dengan nilai (OR= 1,980) setelah dikontrol dengan variabel umur, jumlah anak dan Pendidikan ibu. Jumlah anak yang dimiliki oleh pasangan usia subur merupakan sesuatu nilai yang sangat penting bagi pengambilan keputusan untuk memakai kontrasepsi jangka Panjang